Determination of True Metabolizable Energy Content of Bobwhite Foods - M. E. Spurlock; J. E. Savage (National Quail Symposium Proceedings, 2017)
True metabolizable energy (TME) and nitrogen-corrected true metabolizable energy (TMEn) bioassays were used to determine available energy content of several northern bobwhite (Colinus virginianus) foods. A proximate analysis and trypsin inhibitor (TI) activity were also determined for each food. Corn (Zea mays) was found to contain the highest amount ofTMEn (4.37 kcal/g dry matter) compared with Fayette soybeans (Glycine max; 3.93 kcal/g), Korean lespedeza (Kummerowia stipuki.ceae; 3.73 kcal/g), Marion lespedeza (K. striata; 3.71 kcal/g), tick-trefoil (Desmodium spp.; 3.51 kcal/g), and wild trailing (WI') soybeans (3.24 kcal/g). The higher TMEn value of corn was attributed to its high digestible carbohydrate content and lack of appreciable TI activity.
Keywords: bobwhite; corn; lespedeza; metabolizable energy; nutrition; soybeans; tick-trefoil; trypsin inhibitor